Analysis of cases of deaths from covid-19 in the state of Paraná: A cross-sectional study - Koga , Patricia Midori; de Carvalho , Thays Lienddry Rosa Bergamo; de Carvalho , Wesley Velozo; Tashima , Cristiano Massao; Alarcon, Miriam Fernanda Sanches; Katakura , Edna Aparecida Lopes Bezerra (Seven Editora, 2023)
Introduction: After the first cases of COVID-19 emerged, we realized that some groups of people were more affected than others. When we analyze the cases of the disease and deaths, the literature reports that there is a higher incidence of the disease in the adult population, but the lethality is higher in the elderly. Objective: To analyze the cases of deaths from COVID-19 in the State of Paraná. Method: This is a descriptive, cross-sectional, and retrospective study, with a quantitative approach, based on secondary data in the public domain, made available by the State Health Secretariat of the State of Paraná (SESA-PR), from March 2020 to March 2021. Results: The State of Paraná reported 16,571 cases of deaths from COVID-19, meaning that 2.1% of the cases, over 18 years of age, notified with the disease, had a negative outcome. The disease was more lethal in the elderly (74.6%) than in the adult population (25.3%). When we stratified the deaths of adults and elderly by sex, we observed that in both adults (61.8%) and the elderly (56.8%) the highest number of deaths was in men, compared to adult women (38.1%) and elderly women (43.1%). However, when we stratified the number of cases of deaths by age group and sex in the adult and elderly population, the number of deaths was higher in older men, in the age group between 41 and 59 years, about 80.9% of deaths. In the elderly population, the highest number of deaths also occurred in the male elderly, aged between 70 and 79 years, representing about 36.8% of the deaths. Final considerations: The results of the study suggest that age and gender are variables that may interfere in the establishment of risk groups for the disease and may also be related to different outcomes, especially death. Other results show that when we analyze the distribution of cases of the disease and deaths by age group, in Brazil and worldwide, there is evidence that there is a higher incidence of the disease in the adult population, however, the lethality is higher in the elderly population. Although COVID-19 is less lethal compared to other epidemics caused by the coronavirus, its power of transmissibility is much higher affecting mainly the elderly, men, and those with comorbidities, the findings in this study also show the increase in deaths in men when compared to what was observed in women, which are similar to some literature. DOI:https://doi.org/10.56238/emerrelcovid19-052